Relationship of Work Position to Low Back Pain (LBP) in Convection Tailors - Cigilang Rahmandayu; Darwin Karim; Sri Utami (CV. Rayyan Dwi Bharata, 2023)
Introduction: Low Back Pain (LBP) is a health problem in the form of acute and chronic pain that is felt in the lower back which is usually caused by work, inflammation, degeneration, trauma, and metabolic disorders. One of the jobs with a risk of Low Back Pain (LBP) is a convection sewing worker. because of the long duration of work and the attitude of the tailor. This study aims to identify the relationship between work position and complaints of Low Back Pain (LBP) in convection tailors. Method. This study used a correlational descriptive design with a cross-sectional approach. The research sample consisted of 50 respondents with total sampling. The analysis used was bivariate analysis using the chi-square test. Results. characteristics of the majority of respondents were adults aged 26-45 years as many as 25 people (50%), male (64.0%), had a working duration of 8 hours (66.0%), and had worked 5 years (70% ). The majority of respondents, namely 35 respondents (97.2%) worked in moderate risk positions with high LBP complaints. And 13 respondents (92.9%) experienced complaints of moderate Low Back Pain (LBP) in high-risk work positions. The results of the chi-square test between work positions and complaints of Low Back Pain (LBP), obtained a p value = 0.044 Î± ( 0.05). Conclusion. There is a relationship between work position and LBP complaints from convection tailors in Sail and Payung Sekaki Districts.